258 Clinical evaluation of the novel 'FullStop' tourniquet using real time Doppler ultrasound in a human model. (1st May 2022) - Lyon, R; Earle-Wright, B
Abstract : Background: Major haemorrhage following trauma is a leading cause of preventable death. In the case of major haemorrhage from a limb, early application of a tourniquet can be life-saving. Tourniquets often need to be applied by lay persons, prior to the arrival of emergency medical services, in order to prevent exsanguination. A tourniquet needs to be completely reliable and easy to apply rapidly. We sought to evaluate the novel FullStop tourniquet (Safeguard Medical) in a human model. Method: A standard training session covering the FullStop method of application was provided. The FullStop tourniquet was applied to the upper arm of an adult human. Colour doppler ultrasound was used to identify the radial artery and visualise the radial pulse prior to tourniquet application and then following application. The time to full apply the FullStop was recorded. Successful application was defined as absence of any arterial pulsation on ultrasound. Results: 28 medical professionals participated in the study. They included doctors (n=9), nurses (n=8), medical students (n=5) and paramedics (n=6). Median time to application was 24 seconds (IQR 19–28 s). All (n=28, 100%) applications were successful in achieving complete occlusion of arterial flow in the arm. Conclusion: The FullStop tourniquet was rapid to apply and entirely effective in achieving complete occlusion of arterial flow in the upper limb. Further research is warranted to explore how effective the FullStop would be for lay person responders. Conflict of interest: None declared. Funding: None.